Large single-centre cohort of HSP patients in UK: advantages of deep pheno- typing and longitudinal follow-up. Issue 6 (27th May 2022) - Price, Kitty; Mellor, James; Mcnamara, Mary; Hewamadduma, Channa; Shaw, Pamela; Derott, Christopher Mc-; Hadjivassiliou, Marios
Abstract : Aim: To identify clinical, radiological and instrumented gait correlates predictive of natural history in a cohort of HSP patients. Background: HSP is a rare heterogeneous group of neurodegenerative disorders. We present our experi- ence managing a large cohort of HSP patients in the regional centre for HSP. We believe Sheffield Teaching Hospitals to have the largest cohort in the North of England. Methodology and Results: Our cohort comprises 426 patients, 246 male (57.7%) of which 290 were geneti- cally characterized. The commonest mutation is in SPASTIN (SPG4, 38.3%), whilst REEP1 (SPG31) and SPG11 mutations make up 3.1% and 2.1% respectively. Sheffield also holds the largest cohort of SPG7 patients in the UK (n=54) accounting for 18.6% of genetic HSP. The remainder have mutations in KIF5A, Atlastin, WASHC5, KIAA0196, NIPA1, ARSACS, CYP27A1, CYP7B1, AP4S1, GBA2 and L1CAM. Over 240 patients have had detailed MR imaging which has identified novel features in HSP. Repeated instrumented gait monitoring and cognitive assessments have shown novel clinical markers suggesting disease progression. Conclusion: For rare disorders like HSP, specialised clinics optimise comprehensive longitudinal clinical and radiological data collection for large cohorts. This develops local expertise and helps identify novel radiological and clinically relevant biomarkers, enabling better patient care. klprice1@sheffield.ac.uk